Kết nối độ cao chuẩn xác định từ đo cao thủy chuẩn truyền thống và từ đo cao GPS - Lân, Phạm Hoàng (Vietnam Journal of Earth Sciences, 2012)
SummaryIntergrating the normal heights derived from traditional and GPS - levellingBased on theoretical background of the normal height, the author points out the necessity to provide the same normal ellipsoid for calculation of the height anomaly and the geodetic height in GPS - levelling, and for receiving the normal gravity in normal height determination by using traditional levelling data. Accordingly the problems to be solved for intergrating the normal height values determined by two different methods in Vietnam are also pointed out. Furthermore it is shown that the considered task can be realized now with a mean square difference between two kinds of normal height at level of 0,2 - 0,3 m.